2019
DOI: 10.1088/1367-2630/ab36a9
|View full text |Cite
|
Sign up to set email alerts
|

Collective operations can extremely reduce work fluctuations

Abstract: We consider work extraction from N copies of a quantum system. When the same work-extraction process is implemented on each copy, the relative size of fluctuations is expected to decay as N 1. Here, we consider protocols where the copies can be processed collectively, and show that in this case work fluctuations can disappear exponentially fast in N. As a consequence, a considerable proportion of the average extractable work  can be obtained almost deterministically by globally processing a few copies of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…This indicates that common noise may be also considered for enhancing the performance of small autonomous classical motors, like thermoelectric devices [73] or biomolecular systems [74] described within the framework of stochastic thermodynamics [75]. Nevertheless we notice that although the magnitude of the quantum coherent enhancements compared with their incoherent counterpart is rather modest in this fridge model, we expect that the same mechanism might be enforced in many-body configurations [76][77][78] where this effect may be greatly amplified.…”
Section: Discussionmentioning
confidence: 88%
“…This indicates that common noise may be also considered for enhancing the performance of small autonomous classical motors, like thermoelectric devices [73] or biomolecular systems [74] described within the framework of stochastic thermodynamics [75]. Nevertheless we notice that although the magnitude of the quantum coherent enhancements compared with their incoherent counterpart is rather modest in this fridge model, we expect that the same mechanism might be enforced in many-body configurations [76][77][78] where this effect may be greatly amplified.…”
Section: Discussionmentioning
confidence: 88%
“…Theoretical studies have shown advantages by exploiting collective effects in quantum batteries [23,32,36,41,69,83]. Here, we apply the bounds on work extraction to a simple many-body spin system described by the XY model [18,39,73], which can be investigated experimentally [59,104].…”
Section: The Anisotropic Xy Modelmentioning
confidence: 99%
“…For η = 0, the Hamiltonian (23) reduces to the Dicke model. At the critical point g = √ ω a ω c /2, the system undergoes a well-known normal-superradiant phase transition 80 .…”
Section: A Charging Properties With Interatomic Interactionsmentioning
confidence: 99%
“…Previous work have shown the importance of quantum resources in improving the performances of QBs, such as work extraction [12][13][14][15] , charging power [16][17][18][19] , and energy fluctuation [20][21][22][23][24][25] . In 2013 Alicki and Fannes first proposed that entangling unitary controls acting globally extract in general more work than unitary operations acting on each quantum cell separately 5 .…”
Section: Introductionmentioning
confidence: 99%